Optimal timing of cervical cerclage removal following preterm premature rupture of membranes; a retrospective analysis. (April 2021) - Suff, Natalie; Kunitsyna, Maria; Shennan, Andrew; Chandiramani, Manju
Highlights: Largest retrospective study evaluating woman following cerclage removal or retention after PPROM. Cervical cerclage retention in women following PPROM was associated with a longer latency period to delivery. Cervical cerclage retention in women following PPROM was associated with a non-significant trend towards chorioamnionitis. Abstract: Objective: Preterm prelabour rupture of membranes occurs in over one third of pregnant women with a cervical cerclage in situ. In the setting of preterm prelabour rupture of membranes, clinicians are faced with the difficult decision of the optimal timing for removing the cerclage. We compared the maternal and neonatal outcomes following immediate removal or retention of the cervical cerclage. Study design: Women were retrospectively identified from St Thomas's Hospital Preterm Surveillance clinic database. Asymptomatic women with preterm prelabour rupture of membranes were identified and separated into those that had the cerclage removed and those that had the cerclage retained within 24 h of presentation. Women who were symptomatic at presentation and who delivered within 24 h of presentation were excluded from the analysis. Maternal outcomes measured were latency between preterm prelabour rupture of membranes and delivery, gestation at delivery and maternal chorioamnionitis and infection markers. Neonatal outcomes including birthweight and Apgar scores were also measured. Results: 43 women with cerclage retained for over 24 h following preterm prelabour rupture of membranes were compared to 25 women in whom the cerclage was removed. The latency between preterm prelabour rupture of membranes and delivery was on average 70.4 h longer in women who had their cerclage retained compared to the removed group (p = 0.009). Rates of chorioamnionitis, maternal blood results, neonatal birthweight and Apgar scores did not differ significantly between the two groups, however a trend towards higher rates of chorioamnionitis (60 % vs 45 %) were seen in the retained group. Conclusion: Cervical cerclage retention in women following preterm prelabour rupture of membranes was associated with a longer latency period to delivery and was not significantly associated with any adverse obstetric, maternal or neonatal outcomes. Therefore, in women at risk of spontaneous preterm birth, cerclage retention may be beneficial, however these women and their babies should be monitored closely for any signs of infection. Further prospective randomised controlled studies assessing these outcomes as well as longer-term outcomes in these women and their children are needed.